Memahami Niat Beli di Kalangan Konsumen 3Second: Peran Citra Merek, Pemasaran Media Sosial, dan Pengalaman Pelanggan Berbasis AI (Studi pada Konsumen Brand Fashion Lokal 3Second di Bandung, Indonesia) - Fatimah Rahman; Ayesa Aulia Sofwa; Sanita Putri Yaperta; Megha Sakova (Indo Publishing, 2026)
Digital transformation has reshaped the way consumers interact with brands, making purchase intention no longer influenced solely by brand image, but also by social media marketing and AI-based customer experience. This study aims to examine the effects of Brand Image, Social Media Marketing, and AI-Based Customer Experience on the Purchase Intention of 3Second consumers. A quantitative approach with a causal-associative research design was employed, involving 35 3Second consumers selected through purposive sampling. The data were analyzed using multiple linear regression with IBM SPSS Statistics. The findings indicate that, partially, only Social Media Marketing has a positive and significant effect on Purchase Intention, whereas Brand Image and AI-Based Customer Experience do not have significant effects. However, the three variables jointly have a positive and significant influence on Purchase Intention, explaining 77.4% of its variance. These findings suggest that the effectiveness of social media marketing is the primary driver of consumers' purchase intention toward 3Second, while strengthening brand image and optimizing AI-based customer experience remain essential to supporting an integrated digital marketing strategy. This study contributes to a broader understanding of the factors influencing purchase intention in the local fashion industry in the digital era.